2020
DOI: 10.5194/hess-24-4061-2020
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of snow models to the accuracy of meteorological forcings in mountain environments

Abstract: Abstract. Snow models are usually evaluated at sites providing high-quality meteorological data, so that the uncertainty in the meteorological input data can be neglected when assessing model performances. However, high-quality input data are rarely available in mountain areas and, in practical applications, the meteorological forcing used to drive snow models is typically derived from spatial interpolation of the available in situ data or from reanalyses, whose accuracy can be considerably lower. In order to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 46 publications
5
19
0
Order By: Relevance
“…These findings are confirmed by the work of Terzago et al (2020), where melt models of lower complexity did show higher biases against observations with respect to more complex ones like SNOWPACK. In Terzago et al (2020), high biases for simpler models are related both to their underestimation of snow water equivalent peak values and to the protraction of snow melt season that they reproduce. Maps of summer months in Fig.…”
Section: Panel (A)supporting
confidence: 72%
“…These findings are confirmed by the work of Terzago et al (2020), where melt models of lower complexity did show higher biases against observations with respect to more complex ones like SNOWPACK. In Terzago et al (2020), high biases for simpler models are related both to their underestimation of snow water equivalent peak values and to the protraction of snow melt season that they reproduce. Maps of summer months in Fig.…”
Section: Panel (A)supporting
confidence: 72%
“…This information is crucial to calibrate adaptive strategies to better face climate change effects in alpine ecosystems. It is worth remembering that mountains are among the most sensitive ecosystems to climate change, especially rising temperature, where effects observed more quickly than in other terrestrial habitats [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] and this study could be considered another one concerning the short-term climate change effect on rangelands' and broad-lived forests' phenology in Aosta Valley. In particular, EO data from public and free archives of ready-to-use products such as MOD13Q1 and MOD16A2, proved to support well this type of analysis in spite of their reduced geometric resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [57], Liu et al [58], Hersbach et al [59], Terzago et al [60], and Orsolini et al [61] conducted a comprehensive assessment of snow cover parameters for this dataset, the findings showed that the ERA5 dataset can well capture the spatial distribution of snow cover and a wide range of characteristics of seasonal changes despite its large positive bias. Wang et al [62], Matveeva and Sidorchuk [63], and Yılmaz et al [64]…”
Section: Data 221 Snow Datamentioning
confidence: 93%